Spatiality of groundwater chemical attributes in the municipality of Granito, PE (Research, Society and Development, 2020)
The rational and sustainable exploitation of groundwater is now becoming increasingly important for irrigation purposes. In semi-arid regions, irrigation handled improperly can cause salinization and sodification of soils and increased groundwater scarcity. The knowledge of the spatial behavior of the groundwater chemical quality parameters is essential for an accurate irrigation management. In this work, we sought to evaluate the spatial variability of the chemical attributes of groundwater used in irrigation in the Pernambuco semiarid region. Waters of the municipality of Granito-PE, used for agricultural purposes. were evaluated for chemical attributes: pH, Ca2+, Mg2+, K+, Na+, CE and RAS was calculated. The results were analyzed using descriptive statistics, Person correlation and geostatistics. The groundwater used for irrigation in the municipality of Granito for the mostly part it 95%   saline and 20% have sodium character. With the spatial variability maps, it was possible to identify the zones with greater and lesser salinization potential by using groundwater.